Penguatan Nilai-Nilai Civic Disposition dalam Mencegah Degradasi Moral di SMPN 5 Percut Sei Tuan - Situmorang, Dandi Abram; Salsabila, Tengku; Panggabean, Naulita (Indo-MathEdu Intellectuals Journal, 2024)
This research addresses the issue of moral degradation among teenagers, particularly in the context of SMPN 5 Percut Sei Tuan. This research aims to identify and analyze civic values that are important to prevent moral degradation among students. The research method used is a qualitative approach. Interviews and focus group discussions with educators, parents, and students are used to gather insights into the existing moral landscape and civic values that need to be strengthened. The data obtained will be analyzed using thematic analysis techniques to identify the main themes that emerge from the research results. The research findings revealed that values such as responsibility, empathy, respect and active participation are critical to fostering a positive moral environment. This research contributes to the understanding of how educational institutions can play an important role in shaping adolescents' moral character. The recommendations provided aim to serve as a framework for educators and policy makers to implement effective strategies that not only improve academic achievement but also foster responsible and civic-minded citizens. Ultimately, this study underscores the importance of cultivating civic-minded values as a means to combat moral degradation and promote a healthier and more ethical society